The Sustainable Development Goals (Taylor & Francis, 2022)
There have been significant efforts to implement the Sustainable Development Goals (SDGs) at multiple levels of governance across all regions of the world. However, the manner in which the global governance norms underlying the SDGs are actually being diffused is under-researched and not well understood. This book considers the promotion of the SDGs through the lens of norm diffusion theory, with a focus on three SDG policy areas; health, education and decent work.